A física no ENEM dos anos 2008 e 2009 sob o olhar do movimento: ciência, tecnologia e sociedade - Silva, Márcio Lima da (2016)
The object of these research studies are the items of physical evidence from the Brazilian National Assessment of Secondary Education (ENEM) of the years 2008 and 2009. The purpose of this study is to analyse the level of interface that the items of ENEM physics with the perspective of an education in keeping the MOVEMENT SCIENCE TECHNOLOGY AND SOCIETY (STS). Besides, we intend to contribute to the understanding statements changes in items dealing Physics ENEM the evidence from its reformulation occurred in 2009. The importance given to the ENEM in the educational setting, we can say that the content of their evidence has great influence in the development of curriculum, preparation of teaching materials and teaching practices, indicating ways Physics Teaching. The recasting of the review took place in 2009 can reveal the paths being traveled by the Physics Education in Brazil, and which teaching practices are valued. The theoretical reference used to carry out this work was the STS movement. This movement contributes to an education in which they are articulated not neutral looks, movers and intricate among the tripod STS. This perspective of education can be considered advances towards contribute to the production of learning materials and innovate pedagogical practices. Content analysis is a research technique used. This analysis was enable us to categorize items by interface to the STS movement. To identify these interfaces, we highlight the concepts of interdisciplinary and background present in PARAMETERS NATIONAL CURRICULUM (PCN) and the concept of problematization in a perspective of Freire. As a result of this research, we highlight a clear reduction of interfaces between the statements of Physics and the Movement STS in the years analyzed, so that in 2008, identified 73% of the items analyzed with strong interface while in 2009, we identified only 25% strong interface.